Comparative efficacy of seven exercise interventions for symptoms of depression in college students: A network of meta-analysis. Issue 47 (20th November 2020) - Guo, Shengyu; Liu, Feiyue; Shen, Jing; Wei, Min; Yang, Yan
Abstract: Background: Depression among college students is common, exercise interventions are valued as one of the most widely prescribed interventions for depressed college students, however, it is especially difficult for university administrators to determine which exercise intervention is most effective, and efficacy of exercise interventions among depressed college students have not been evaluated. Objectives: To systematically review and compare the efficacy of 7 exercise interventions for decrease symptoms of depression in college students. Method: A network of meta-analysis (NMA) was conducted to fill the objectives. Five relatived electronic databases were searched for the related articles. Eligibility criteria: Randomized controlled trials comparing the efficacy of 7 Exercise interventions with usual care of college students with depression were included in the review. Main outcomes: The primary outcome of the present study was standardized mean difference (SMD) and the mean change of depressive symptoms. Results: Fourteentrials were identified, including 2010 depressed college students. The result of direct meta-analysis of this review indicated exercise interventions overall had a significantly lower mean depression scores (SMD = −1.13) when compared with usual care. The result of NMA indicated when comparing with badminton intervention, yoga (SMD = −7.7, 95%CI: −14 to −0.93) and Tai chi (SMD = −9.4, 95%CI: −16 to −2.7) can significantly decrease depression scores of the depressed college students. The rank of 7 exercise interventions with respect to efficiently decrease symptom of depressed undergraduates was Tai chi > Yoga > Volleyball > Dance > Run > Basketball > Badminton, respectively. Conclusions: Tai chi exhibited the highest probability that became the most efficacy intervention among the comparions, and Yoga showed the second most effectiveness to alleviate depressive symptoms of depressed college students, and dance ranks the third, followed by run, volleyball, basketball, and badminton respectively.